Alterations in the odor profile of plants in cultivar mixtures affect aphid host-location behavior - Tous-Fandos, Alba; Gallinger, Jannicke; Enting, Arnoud; Chamorro-Lorenzo, Lourdes; Sans Serra, F. Xavier; Ninkovic, Velemir (Frontiers in Plant Science, 2023)
Cultivar mixture effect on aphid control is attributed to the masking or the alteration of host-preferred cultivar odor cues. However, the physiologic mechanisms underlying remain unclear. This study assesses the alteration in the volatile emission of wheat cultivars when grown together (Florence-Aurora and Forment; Florence-Aurora and Montcada) and consequences for olfactory preference of aphids. Volatile organic compounds from wheat plants grown in a laboratory under mixture or monoculture conditions were collected and analyzed. The odor profiles of Florence-Aurora and Montcada were not distinguishable from each other. Whereas the odors of Florence-Aurora and Forment grown in monocultures differed significantly from the odor emitted by their mixture. Florence-Aurora and Forment mixture induced plant physiological responses affecting the emission of single volatile compounds and consequently altered VOC ratios. English grain aphids (Sitobion avenae) were less attracted to the odor of Florence-Aurora and Forment when grown as a mixture compared to a mixture of the odors from Florence-Aurora and Forment monocultures. Moreover, aphids avoided the odor from Florence-Aurora and Forment mixture and preferred clean air, while the odor from Florence-Aurora and Montcada mixture was more attractive for aphids than clean air. This study highlights the beneficial effect of intraspecific plant diversity on aphid control by alteration of plant odors in response to plant-plant interactions. Emission of less attractive odor cues consequently affect plant-aphid interaction, hence are likely to impair aphid host finding behavior. This effect is exclusive to certain cultivar mixtures, supporting the right neighbor idea.